Near-infrared organic materials and emerging applications - Wang, Zhi Yuan (Boca Raton : Taylor & Francis, 2013)
'Highlighting emerging applications of near-infrared (NIR) organic materials that are currently receiving great attention due to their potential use in optical communications, biomedicine, and camouflage materials, this cutting-edge book reviews important recent advances in an accessible style suitable for researchers and graduates in the field on organic/polymer solar cells, optical communications, and advanced optoelectronics. A beacon in the field literature, this comprehensive work discusses several areas of research and development including thermal control and emission detectors in which new materials are needed that can absorb, emit, and interact with NIR light'--
ch. 1. Introduction -- ch. 2. Molecular design and energy gap tuning -- ch. 3. Near-infrared organic compounds -- ch. 4. Near-infrared absorbing polymers -- ch. 5. Emerging applications of near-infrared organic materials.
Includes bibliographical references and index.
Mode of access: World Wide Web.
Keywords: Infrared technology -- Materials; Organic compounds -- Spectra; Near infrared spectroscopy